2021
DOI: 10.3390/pharmacy9040171
|View full text |Cite
|
Sign up to set email alerts
|

Community Pharmacist-Led Interventions to Improve Preconception and Pregnancy Health: A Systematic Review

Abstract: Background: Community pharmacist-led interventions are effective in improving health outcomes; however, their impact in improving preconception and pregnancy health is not clear. This study evaluated the effectiveness of community pharmacist-led interventions which aimed to improve health outcomes of preconception and pregnant women. Methods: A systematic review of the literature, consistent with PRISMA guidelines, was performed. Five electronic databases were searched up to February 2021. Results: Four studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Together, the findings provide evidence for the potential benefits of community pharmacyled interventions for women's health. 17 OP is common amongst post-menopausal women and often has no symptoms before fractures; therefore, early detection and prevention via screening programmes can be an effective strategy for reducing fractures and associated mortality and healthcare costs. 29 Currently for suspected OP, a combination of tests are used to determine bone Patient satisfaction with the education session was high, with a median satisfaction rating of 5 (a range of 4 to 5) at 3 months, and a median satisfaction rating of 4 (a range of 3 to 5) at 1 year, on a 5-point satisfaction rating scale At 3 months, 4 women (20%) responded that they changed their diet and exercise routine, 2 (10%) changed their prescription medication and 7 (35%) started taking vitamins or minerals as a result of the session At 1 year, 6 women (40%) responded that they changed their diet, 5 (31%) changed their exercise routine and 2(13%) changed their prescription medication and started taking vitamins or minerals as result of the session Abbreviations: OP, osteoporosis; OPe, osteopenia; CI, confidence interval; SD, standard deviation; MoM, management of menopause.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Together, the findings provide evidence for the potential benefits of community pharmacyled interventions for women's health. 17 OP is common amongst post-menopausal women and often has no symptoms before fractures; therefore, early detection and prevention via screening programmes can be an effective strategy for reducing fractures and associated mortality and healthcare costs. 29 Currently for suspected OP, a combination of tests are used to determine bone Patient satisfaction with the education session was high, with a median satisfaction rating of 5 (a range of 4 to 5) at 3 months, and a median satisfaction rating of 4 (a range of 3 to 5) at 1 year, on a 5-point satisfaction rating scale At 3 months, 4 women (20%) responded that they changed their diet and exercise routine, 2 (10%) changed their prescription medication and 7 (35%) started taking vitamins or minerals as a result of the session At 1 year, 6 women (40%) responded that they changed their diet, 5 (31%) changed their exercise routine and 2(13%) changed their prescription medication and started taking vitamins or minerals as result of the session Abbreviations: OP, osteoporosis; OPe, osteopenia; CI, confidence interval; SD, standard deviation; MoM, management of menopause.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent review evaluated the effectiveness of community pharmacy-led interventions which aimed to improve health of preconception and pregnant women. 17 It showed that community pharmacy-led interventions improved adherence to iron supplements, aided in smoking cessation and increased awareness and use of folic acid supplements. Together, the findings provide evidence for the potential benefits of community pharmacy-led interventions for women's health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research demonstrated the benefit of community pharmacy-delivered interventions in improving iron status and smoking cessation in pregnant women while increasing awareness and use of folic acid supplements in preconception women. [8] Indeed, a recent study to raise awareness of preconception care (PCC) within community pharmacies in Northern Ireland was shown to be both feasible and acceptable to women and pharmacy staff. [9] The experiences of community pharmacists in providing medication advice for pregnant women are well documented, [10,11] however, there is a paucity of studies assessing their experiences and attitudes towards providing advice to preconception and pregnant women beyond medication usage.…”
Section: Introductionmentioning
confidence: 99%